An approximate analytic solution for isentropic flow by an inviscid gas model (Archives of Mechanics - Test, 2014)
The aim of the present analysis is to apply the modified decomposition method (MDM) for the solution of isentropic flow of an inviscid gas model (IFIG). The modification form based on a new formula of Adomian’s polynomials (APs). The new approach provides the solution in the form of a rapidly convergent series with easily computable components and not at grid points. The proof of convergence of MDM applied to such systems is introduced with a bound of the error. Using suitable initial values, the solution of the system has been calculated and represented graphically. An analytic continuous solution with high accuracy was obtained.